Pembuatan Obat Nyamuk Herbal Sebagai Alternatif Pembasmi Nyamuk Di Desa Sopu Kabupaten Sigi - Ayu Wulandari; Monica Sandra; Suci Rahmayanti (Duta Abdimas, 2022)
Aedes is a genus of mosquitoes that often cause health problems. The genus Aedes is a biological vector of DHF (Dengue Hemorrhagic Fever). Concern over the current outbreak of DHF (Dengue Hemorrhagic Fever) has resulted in the use of many chemical-based insect repellents such as insecticides to eradicate mosquitoes. However, these things can cause toxic residues that are harmful to human and livestock health, environmental pollution and can cause unwanted effects such as natural enemies if used continuously and for a long time. Currently, electric mosquito repellent is one of the people's choices. Therefore, to make people aware of the importance of high selectivity in using mosquito repellent that is safe for health and the environment, it is necessary to have community service regarding and training regarding the use and manufacture of herbal mosquito repellent. Hernal mosquito repellent is made from a mixture of natural ingredients that contain nicotinic substances that can protect us from mosquitoes. The materials used for the manufacture of mosquito repellent are very easy to find or easy to obtain. Because it only uses orange peel and garlic as the basic ingredients. The method of manufacture is also very easy so that it is also easy to apply among housewives. The manufacture of herbal mosquito repellent made from garlic and orange peel is an alternative as an insect repellent that is safe for health in terms of the ingredients